(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
As a conference and tourist resort hub, Kashmir is one of India’s most rapidly expanding states. There is a lot of building work going on right now. It’s also projected that there will be a lot more building in the future. However, there has been relatively little research on the engineering qualities of Kashmir valley’s soils. Shear strength, or the capacity to resist sliding along internal surfaces inside a soil mass, is one of the most essential engineering qualities of soil. All stability assessments in geotechnical engineering, whether they be for foundations, slopes of cuttings, or earth dams, require a fundamental understanding of this soil engineering feature. The shear strength parameters of Kashmir’s alluvial soil are going to be investigated in this study. The shear strength parameters (c and Ф) are investigated using disturbed soil samples that have been remoulded with various densities and water contents to imitate field conditions. Infrastructural developments have now progressed in Jammu and Kashmir and strength evaluation of peat remains complex and uncertain. Considering failures of infrastructures resulting from inappropriate measurement of peat shear strength, this research paper present on the shear strength of peat and the modification of existing testing methods to assess its strength in the laboratory and on the field. The initial part of this research is the laboratory testing of peat specimens. Scanning electron microscopy (SEM), triaxial tests are conducted to characterise the morphology, compressibility and shear strength properties of peat. The results of the microstructural and compressibility analysis are presented together with the triaxial stress-strain analysis. The analysed results show the effect of decomposition on peat and shear strength characteristics.